Prevalence and risk factors for efavirenz-based antiretroviral treatment-associated severe vitamin D deficiency: a prospective cohort study - Nylén, Hanna; Habtewold, Abiy; Makonnen, Eyasu; Yimer, Getnet; Bertilsson, Leif; Burhenne, Jürgen; Diczfalusy, Ulf; Aklillu, Eleni (Medicine, 2016)
Initiation of efavirenz-based combination antiretroviral therapy (cART) is associated with Vitamin D deficiency, but the risk factors including efavirenz pharmacokinetics for cART-induced severe vitamin D deficiency (SVDD) and the impact of anti-tuberculosis (TB) cotreatment are not explored. We investigated the prevalence of SVDD in HIV and TB-HIV coinfected patients and associated risk factors for treatment-induced SVDD. - Treatment-naïve Ethiopian HIV patients with (n = 102) or without (n = 89) TB co-infection were enrolled prospectively and received efavirenz-based cART. In TB-HIV coinfected patients, rifampicin-based anti-TB treatment was initiated 4 or 8 weeks before starting cART. Plasma 25-hydroxyvitamin D (25 [OH]D), cholesterol and 4-beta hydroxycholesterol concentrations were measured at baseline, 4th, 16th, and 48th week of cART. Plasma efavirenz concentrations were determined at 4th and 16th weeks of cART. - TB-HIV patients had significantly lower plasma 25 (OH)D3 levels than HIV-only patients at baseline. TB co-infection, low Karnofsky score, high viral load, and high CYP3A activity as measured by plasma 4β-hydroxycholesterol/cholesterol ratios were significant predictors of low 25 (OH)D3 levels at baseline. In HIV-only patients, initiation of efavirenz-based cART increased the prevalence of SVVD from 27% at baseline to 76%, 79%, and 43% at 4th, 16th, and 48th weeks of cART, respectively. The median 25 (OH)D3 levels declined from baseline by −40%, −50%, and −14% at 4th, 16th, and 48th weeks of cART, respectively. - In TB-HIV patients, previous anti-TB therapy had no influence on 25 (OH)D3 levels, but the initiation of efavirenz-based cART increased the prevalence of SVDD from 57% at baseline to 70% and 72% at the 4th and 16th weeks of cART, respectively. Median plasma 25 (OH)D3 declined from baseline by −17% and −21% at week 4 and 16 of cART, respectively. - Our results indicate low plasma cholesterol, high CYP3A activity, and high plasma efavirenz concentrations as significant predictors of early efavirenz-based cART-induced vitamin D deficiency. Low plasma 25 (OH)D3 level at baseline is associated with TB co-infection and HIV diseases progression. Initiation of efavirenz-based cART is associated with high incidence of SVDD, whereas rifampicin based anti-TB therapy co-treatment has no significant effect. Supplementary vitamin D during cART initiation may be beneficial for HIV patients regardless of TB coinfection.